Promotion of the equity and social cohesion in the University of Costa Rica - Washburn-Madrigal, Stephanie (2013)
This article refers to the results obtained in the first phase of work of the Red Alfa III as the Inter-university Framework Program for Equity and Social Cohesion Policies in Higher Education, with the University of Costa Rica, as a partner institution. It includes the analysis of the actions for promoting equity and social cohesion, developed by the University as an institution of higher education. It concludes that although the institution has rules enough resources to promote justice and equality in its own community from teaching, research, social action and student life, other psychosocial conditions are not being fulfilled in an appropriate way.